2018
DOI: 10.1186/s13104-018-3159-2
|View full text |Cite
|
Sign up to set email alerts
|

Sero-prevalence of HBsAg in naive HIV-infected patients in a rural locality of Cameroon

Abstract: ObjectiveThis study was performed in order to fill the gap of knowledge regarding sero-epidemiology of hepatitis B virus (HBV) amongst Human Immunodeficiency virus (HIV)-infected patients and to assess the risk factors associated with HBV co-infection in a rural locality of Cameroon. A retrospective and cross-sectional study was carried out from January 2008 to April 2014 within the Mfou District Hospital. Naive HIV-infected patients were enrolled in the study and tested for hepatitis B surface antigen (HBsAg)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 14 publications
(15 reference statements)
0
4
1
Order By: Relevance
“…The co-infection was 2.5% in their study population [10]. Our prevalence is low compared to Zoufaly et al and Molu et al who reported the prevalences of 12.6% in 2012% and 8.99% in 2018 respectively [6,11]. One of the most likely causes of the high prevalence of HBV-HIV co-infection is that both viruses have similar transmission pathways [12].…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…The co-infection was 2.5% in their study population [10]. Our prevalence is low compared to Zoufaly et al and Molu et al who reported the prevalences of 12.6% in 2012% and 8.99% in 2018 respectively [6,11]. One of the most likely causes of the high prevalence of HBV-HIV co-infection is that both viruses have similar transmission pathways [12].…”
Section: Discussioncontrasting
confidence: 46%
“…Its seroprevalence in Congo was 3.2% between 2009 and 2013 [5]. Molu et al in 2018 reported an 8.9% prevalence of HBV infection in HIV-infected people in Cameroon [6]. In Congo, the exact prevalence of hepatitis B in the HIV population has not been accurately established.…”
Section: Introductionmentioning
confidence: 99%
“…In Cameroon, approximately 10% of HIV-infected patients are positive for HBsAg [9,[11][12][13]. National guidelines recommended HBsAg testing before starting ART in HIV-infected patients who show signs and symptoms of liver disease [14].…”
Section: Study Settingmentioning
confidence: 99%
“…Further, a retrospective control laboratory-based study showed an HBV rate of 16.2% among HIV patients from a more rural area of the country [14]. A study carried out on HIV patients in the Mfou community in Cameroon showed a Prevalence of HBsAg of 8.9% [15]. It is worth noting that this study did not present information about demographic risk factors, stage of HIV infection, and viral load.…”
Section: Introductionmentioning
confidence: 66%